Pengaruh Persepsi Peserta Didik Mengenai Pengelompokan Kelas yang Dimoderasi Keaktifan Belajar dan Implikasinya Pada Hasil Belajar Mata Pelajaran Ekonomi - Zahra, Hanifa Aulia; Gumilar, Gugum; Aisyah, Iis (Universitas Batanghari Jambi, 2024)
This research was conducted because of the low learning outcomes in class X economics subjects with the phenomenon found in the form of class grouping carried out by school management. So the research aims to determine the influence of students' perceptions regarding class grouping on learning activity and embed it in learning outcomes. The research was conducted using a survey method with class X students as the population, the sampling technique used was proportional random sampling with a total of 209 students. Data was obtained through a questionnaire with regression analysis moderation techniques. The results of this research are: students' perceptions regarding class grouping have a significant effect on learning activity, learning activity can strengthen the relationship between students' perceptions regarding class grouping and learning outcomes, students' perceptions regarding class grouping have an influence on learning activity and have implications for learning outcomes. economics lesson